A case of massive refractory diarrhea in a patient with COVID‐19. Issue 1 (5th October 2022) - Shimizu, Kentaro; Hirata, Haruhiko; Tokuhira, Natsuko; Ueda, Akiko; Motooka, Daisuke; Nakamura, Shota; Ogura, Hiroshi
Abstract : Background: The new coronavirus disease (COVID‐19) causes gastrointestinal symptoms as well as respiratory symptoms. Case Presentation: A 60‐year‐old man was transferred with respiratory difficulty. He was diagnosed as having COVID‐19 and was intubated and placed on mechanical ventilation. He suffered from diarrhea from day 12 and produced a maximum of approximately 6, 384 mL/day of watery diarrhea on day 21. He required massive transfusion. Adsorbents and pectin‐containing oligomeric formulas were administered, which decreased the amount of diarrhea. Fecal metagenomic analysis showed the proportions of the genera Enterococcus and Staphylococcus were the most dominate at the genus level. The proportion of Bacteroidetes was <1%. Thereafter, his diarrhea decreased to several times, and he was transferred to another ward on day 104. Conclusion: Therapy for intestinal complications as well as that for pneumonia might be important in treating COVID‐19. Abstract : Fecal Gram stain shows that simplified bacteria cover the field instead of normal bacteria. (Upper left) Healthy control. (Upper right) Enterococcus. (Lower left) Fungi. (Lower right) Klebsiella pneumoniae.